Safety evaluation of the food enzyme glucose oxidase from a genetically modified Aspergillus oryzae (strain NZYM-KP) - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (2018)
The food enzyme is a glucose oxidase (beta-d-glucose:oxygen 1-oxidoreductase; EC 1.1.3.4) produced with a genetically modified strain of Aspergillus oryzae strain NZYM-KP by Novozymes A/S. The genetic modifications do not give rise to safety concerns. The food enzyme does not contain the production organism or DNA; therefore, there is no safety concern for the environment. The glucose oxidase is intended to be used in baking processes. Based on the maximum use levels recommended and individual consumption data from the EFSA Comprehensive European Food Consumption Database, dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be up to 0.156 mg TOS/kg body weight (bw) per day in European populations. The food enzyme did not induce gene mutations in bacteria or chromosome aberrations in human lymphocytes. The subchronic toxicity was assessed by means of a repeated dose 90-day oral toxicity study in rodents. A no-observed-adverse-effect level was derived (341 mg TOS/kg bw per day), which compared with the estimated dietary exposure results in a sufficiently high margin of exposure. The allergenicity was evaluated by comparing the amino acid sequence to those of known allergens and one match with a fungal contact allergen was found. The Panel considered that, under the intended condition of use, the risk of allergic sensitisation and elicitation reactions by dietary exposure cannot be excluded, but the likelihood is considered low. Based on the microbial source, the genetic modifications, the manufacturing process, the compositional and biochemical data, the estimated dietary exposure and the findings in the toxicological studies, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.